The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.cej.2014.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Correlating the photocatalytic activity and the optical properties of LiVMoO6 photocatalyst under the UV and the visible region of the solar radiation spectrum

Abstract: Citation: HURTADO, L. ...et al., 2015. Correlating the photocatalytic activity and the optical properties of LiVMoO6 photocatalyst under the UV and the visible region of the solar radiation spectrum. Chemical Engineering Journal, 262, pp. 1284-1291. Additional Information:• This paper was accepted for publication in the journal Chemical En-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 27 publications
0
4
0
2
Order By: Relevance
“…It is worth noticing that the catalyst with the highest extinction coefficient values β = σ + κ (TiO 2 DP 25) produces higher values of LVREA at the same catalyst concentration. The values of LVREA obtained by LiVMoO 6 catalyst are smaller than the values obtained by TiO 2 catalyst; however, the special interest on LiVMoO 6 catalyst resides on that it presents catalytic activity even in the visible spectrum [31].…”
Section: System 2 (Photo-crec Ii)mentioning
confidence: 70%
See 1 more Smart Citation
“…It is worth noticing that the catalyst with the highest extinction coefficient values β = σ + κ (TiO 2 DP 25) produces higher values of LVREA at the same catalyst concentration. The values of LVREA obtained by LiVMoO 6 catalyst are smaller than the values obtained by TiO 2 catalyst; however, the special interest on LiVMoO 6 catalyst resides on that it presents catalytic activity even in the visible spectrum [31].…”
Section: System 2 (Photo-crec Ii)mentioning
confidence: 70%
“…The employed catalyst was LiVMoO 6 , and a detailed characterization has been previously reported [31]. The characteristics of the system are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…where is the absorption coefficient and is the scattering coefficient. These optical parameters are related to the properties of the photocatalyst under irradiation and therefore, they are key to assess the photocatalytic activity of semiconductors regardless of the reactor set-up employed since they allow to understand the photon absorption rate of the semiconductor [45]. It can be concluded that from the optical point of view, TiO2/Pt Therefore, the enhancement of the photocatalytic activity due to electron-hole lifetime extension seems to be the main argument supported by the obtained results.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…The concentration of total organic carbon (TOC) of each sample was measured in a Shimadzu Total Organic Carbon Analyzer (model CPH ) fitted with an autosampler [19].…”
Section: Analytic Methodsmentioning
confidence: 99%